The Use of Artificial Intelligence (ChatGPT) in Islamic Education: An Analysis of Challenges, Opportunities, and Ethical Considerations Based on Maqasid Shariah - Ahmad Taha, Jazli Zakwan; Sulaiman, Siti Zhuhharrina; Ajmain@Jima'ain, Muhammad Talhah (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
Rapid advancements in artificial intelligence (AI) have driven various innovations in education, including Islamic Education. ChatGPT, a generative language model developed by OpenAI, offers significant potential in supporting teaching and learning. This study examines the integration of ChatGPT in Islamic Education through an analysis of opportunities, challenges, and ethical considerations. In terms of opportunities, ChatGPT can accelerate access to knowledge, assist independent research, and support student-centered learning. The identified challenges include information accuracy, the risk of excessive dependence, and issues related to academic ethics violations. Ethical aspects are explored from a Shariah perspective, emphasizing the principles of Maqasid Shariah and the etiquette of knowledge seekers. This study employs a qualitative approach through document content analysis to identify key themes related to AI integration in Islamic Education. The findings highlight the need to formulate educational policies, provide professional training for educators, and develop AI usage guidelines grounded in Islamic values. Awareness of these opportunities and challenges is essential to ensure the responsible utilization of ChatGPT, thereby enhancing the delivery of religious knowledge and shaping Muslim students who are knowledgeable, well-mannered and ethical in line with the demands of the digital era.